SYNTHESIS OF SILICA GEL FROM GLASS WASTE AND ITS APPLICATION ON SOLID PHASE EXTRACTION OF Pb(II) CATIONS - Novisatri, M.B.; Priyambodo, E.; Sunarto, S. (Indonesian Journal of Chemistry and Environment, 2018)
Waste glass is one of inorganic wastes which are significant in Indonesia and has not been handled properly. The high content of SiO2 in the glass waste allowed to be processed into silica gel through sol-gel methods. In this research, waste glass was destructed into micro size particles. After that, it was reacted with a sodium hydroxide solution, thus forming a solution of sodium silicate. Silica gel was obtained by reacting sodium silicate with hydrochloric acid. After a silica gel obtained, silica gel is dried and then characterized using infrared spectrophotometry. Using a glass column, silica gel is used as solid phase on solid phase extraction in terms of preconcentration of Pb(II) cations. Based on this research, preconcentration of Pb(II) cations by solid phase extraction using silica gel from glass waste is an effective method.